Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Let's evaluate the piecewise function [tex]\( f(x) \)[/tex] at the specified points to determine which statements are true. The piecewise function is defined as follows:
[tex]\[ f(x)=\left\{\begin{array}{c} -x+1, \quad x<0 \\ -2, \quad x=0 \\ x^2-1, \quad x>0 \end{array}\right\} \][/tex]
1. Evaluating [tex]\( f(-2) \)[/tex]:
Since [tex]\( -2 < 0 \)[/tex], we use the first part of the piecewise function [tex]\( f(x) = -x + 1 \)[/tex]:
[tex]\[ f(-2) = -(-2) + 1 = 2 + 1 = 3 \][/tex]
So, [tex]\( f(-2) = 3 \)[/tex]. Therefore, statement A, [tex]\( f(-2) = 0 \)[/tex], is incorrect.
2. Evaluating [tex]\( f(4) \)[/tex]:
Since [tex]\( 4 > 0 \)[/tex], we use the third part of the piecewise function [tex]\( f(x) = x^2 - 1 \)[/tex]:
[tex]\[ f(4) = 4^2 - 1 = 16 - 1 = 15 \][/tex]
So, [tex]\( f(4) = 15 \)[/tex]. Therefore, statement B, [tex]\( f(4) = 7 \)[/tex], is incorrect.
3. Evaluating [tex]\( f(-1) \)[/tex]:
Since [tex]\( -1 < 0 \)[/tex], we use the first part of the piecewise function [tex]\( f(x) = -x + 1 \)[/tex]:
[tex]\[ f(-1) = -(-1) + 1 = 1 + 1 = 2 \][/tex]
So, [tex]\( f(-1) = 2 \)[/tex]. Therefore, statement C, [tex]\( f(-1) = 2 \)[/tex], is correct.
4. Evaluating [tex]\( f(1) \)[/tex]:
Since [tex]\( 1 > 0 \)[/tex], we use the third part of the piecewise function [tex]\( f(x) = x^2 - 1 \)[/tex]:
[tex]\[ f(1) = 1^2 - 1 = 1 - 1 = 0 \][/tex]
So, [tex]\( f(1) = 0 \)[/tex]. Therefore, statement D, [tex]\( f(1) = 0 \)[/tex], is correct.
In summary, the true statements are:
- Statement C: [tex]\( f(-1) = 2 \)[/tex]
- Statement D: [tex]\( f(1) = 0 \)[/tex]
Therefore, the correct statements are C and D.
[tex]\[ f(x)=\left\{\begin{array}{c} -x+1, \quad x<0 \\ -2, \quad x=0 \\ x^2-1, \quad x>0 \end{array}\right\} \][/tex]
1. Evaluating [tex]\( f(-2) \)[/tex]:
Since [tex]\( -2 < 0 \)[/tex], we use the first part of the piecewise function [tex]\( f(x) = -x + 1 \)[/tex]:
[tex]\[ f(-2) = -(-2) + 1 = 2 + 1 = 3 \][/tex]
So, [tex]\( f(-2) = 3 \)[/tex]. Therefore, statement A, [tex]\( f(-2) = 0 \)[/tex], is incorrect.
2. Evaluating [tex]\( f(4) \)[/tex]:
Since [tex]\( 4 > 0 \)[/tex], we use the third part of the piecewise function [tex]\( f(x) = x^2 - 1 \)[/tex]:
[tex]\[ f(4) = 4^2 - 1 = 16 - 1 = 15 \][/tex]
So, [tex]\( f(4) = 15 \)[/tex]. Therefore, statement B, [tex]\( f(4) = 7 \)[/tex], is incorrect.
3. Evaluating [tex]\( f(-1) \)[/tex]:
Since [tex]\( -1 < 0 \)[/tex], we use the first part of the piecewise function [tex]\( f(x) = -x + 1 \)[/tex]:
[tex]\[ f(-1) = -(-1) + 1 = 1 + 1 = 2 \][/tex]
So, [tex]\( f(-1) = 2 \)[/tex]. Therefore, statement C, [tex]\( f(-1) = 2 \)[/tex], is correct.
4. Evaluating [tex]\( f(1) \)[/tex]:
Since [tex]\( 1 > 0 \)[/tex], we use the third part of the piecewise function [tex]\( f(x) = x^2 - 1 \)[/tex]:
[tex]\[ f(1) = 1^2 - 1 = 1 - 1 = 0 \][/tex]
So, [tex]\( f(1) = 0 \)[/tex]. Therefore, statement D, [tex]\( f(1) = 0 \)[/tex], is correct.
In summary, the true statements are:
- Statement C: [tex]\( f(-1) = 2 \)[/tex]
- Statement D: [tex]\( f(1) = 0 \)[/tex]
Therefore, the correct statements are C and D.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.